Development and Evaluation of a Three-Way Flexible Cannula for Tracheostomy Recovery - Christopher René Torres-SanMiguel (Fluids)
The use of implants in the trachea is increasing in respiratory diseases as an alternative to address pathological problems with airway obstruction. This article presents the design and development of a three-way cannula and its evaluation in a testbed capable of emulating the human breathing cycle. The new tracheal cannula allows airflow through a third duct (vertical one) towards the vocal folds, enabling phonation. The testbed assesses Total Lung Capacity (TLC) and endotracheal pressure by considering the cannula inside a replica of a trachea. The flow is generated by a mechanism composed of electronic elements, and the implementation of instruments for measuring pressure and lung capacity enables the visual and continuous collection of data. The three-way cannula offers improvements in airway capacity, with an average of up to 1.766 L of airflow and a pressure of 17.083 mbar. The airflow at the upper branch allows for improvement, enabling the patient to phonate even with the implant in place, while preserving patency due to the biocompatibility and elasticity of platinum silicone.